High Prevalence of Ultrasound Verified Enthesitis in Patients With Inflammatory Bowel Disease With or Without Spondylarthritis - Husic, Rusmir; Lackner, Angelika; Kump, Patrizia Katharina; Högenauer, Christoph; Graninger, Winfried; Dejaco, Christian (Frontiers in Medicine, 2021)
Background: Inflammatory bowel disease (IBD) is closely associated with spondylarthritis (SpA) and enthesitis, as an important feature of SpA, is a common extraintestinal manifestation of IBD. Enthesitis may be clinically silent in a high proportion of patients with IBD without clinical signs or a diagnosis of SpA. Objectives: The aim of this study was to compare the prevalence of ultrasound (US) verified enthesitis in IBD patients with and without SpA, with patients with irritable bowel syndrome (IBS) and healthy subjects (HC) serving as controls. Methods: IBD patients with or without SpA, patients with IBS and HC were prospectively recruited and clinically assessed. Ultrasound examination was performed at 14 entheses. The ultrasound abnormalities were scored according to the Madrid Ankylosing Spondylitis Enthesitis Index (MASEI). Results: We included 33 IBD patients without SpA, 14 IBD patients with SpA, 26 IBS patients and 18 HC. Higher MASEI scores were found in patients with IBD without SpA (median 21.0 range (8.0-53.0)] and IBD associated SpA [33.0 (8-50)] than in IBS patients [10.5 (0-42.0)-p<0.001 for both comparison] and HC [12.0 (2.0-38.0)-p<0.01]. PD, enthesophytes and erosions were more common in patients with IBD with or without SpA as compared to IBS patients and HC. IBD patients with SpA compared to IBD without SpA demonstrated significant higher prevalence of erosion and structural irregularity and consequently significant higher MASEI (p<0.05 for all comparison). Conclusions: Ultrasound verified enthesitis is more common in patients with IBD with or without SpA as compared to patients with IBS or HC.